Effect of anaemia on the diagnosis of rheumatic heart disease using World Heart Federation criteria. (20th June 2019) - Klein, Jennifer H.; Beaton, Andrea; Tompsett, Alison; Wiggs, Justin; Sable, Craig
Abstract: Background: There is overlap between pathological mitral regurgitation seen in borderline rheumatic heart disease using World Heart Federation echocardiography criteria and physiologic regurgitation found in normal children. One possible contributing factor is higher rates of anaemia in endemic countries. Objective: To investigate the contribution of anaemia as a potential confounder in the diagnosis of rheumatic heart disease detected in echocardiographic screening. Method/Design: A novel Server 2012 data warehouse tool was used to incorporate haematology and echocardiography databases. The study included a convenience sample of patients from 5 to 18 years old without structural or functional heart disease that had a haemoglobin value within 1 month prior to an echocardiogram. Echocardiogram images were reviewed to determine presence or absence of World Heart Federation criteria for rheumatic heart disease. The rate of rheumatic heart disease among anaemic and non-anaemic children according to gender- and age-based norms groups was compared. Results: Of the 935 patients who met the study inclusion criteria, 406 were classified as anaemic. There was no difference in the rate of echocardiograms meeting criteria for borderline rheumatic heart disease in anaemic (2.0%, 95% CI 0.6–3.3%) and non-anaemic children (1.3%, 95% CI 0.3–2.3%). However, there was a statistically significant increase in rates of mitral regurgitation of unclear significance among anaemic versus non-anaemic patients (8.6 versus 3.6%; p = 0.0012). Conclusion: Anaemia does not increase the likelihood of meeting echocardiographic criteria for borderline rheumatic heart disease. Future studies should evaluate for the correlation between anaemia and mitral regurgitation in endemic settings.